2018
DOI: 10.1055/s-0038-1636997
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Shwachman–Diamond Syndrome who Presented with Hypotonia

Abstract: We present a patient with failure to thrive and severe hypotonia, who was initially suspected of having a neurometabolic disease but later diagnosed as Shwachman-Diamond syndrome (SDS), which was genetically confirmed. SDS is a multisystemic disease, which is characterized by exocrine pancreatic deficiency, bone marrow dysfunction with increased risk for malignant transformation, and skeletal abnormalities. It should be included in differential diagnosis of patients with failure to thrive and unexplained neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…Some patients had osteoporosis, enamel dysplasia, or cartilage with metaphyseal dysplasia. Some patients were found to have neurological, learning, and/or behavioral disorders [ 26 ]. Children with SDS can have significant limitations in academic performance, advanced language skills, intellectual reasoning and perception, including reasoning and visual motor skills [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients had osteoporosis, enamel dysplasia, or cartilage with metaphyseal dysplasia. Some patients were found to have neurological, learning, and/or behavioral disorders [ 26 ]. Children with SDS can have significant limitations in academic performance, advanced language skills, intellectual reasoning and perception, including reasoning and visual motor skills [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some patients had osteoporosis, enamel dysplasia, or cartilage with metaphyseal dysplasia. Some patients were found to have neurological, learning, and/or behavioral disorders [26].…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] Many children with SDS suffer from neurological, learning, and/or behavioral difficulties. [ 5 ] Studies have found that patients with SDS may have significant barriers to advanced language skills, intellectual reasoning, academic performance, and perception, including reasoning and visual motor skills. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…У представленной пациентки были легкие гепатомегалия и повышение уровня трансаминаз. Хотя эти нарушения со временем разрешаются, они могут затруднить дифференциальную диагностику [10]. Нейтропения может быть важным ключом к постановке диагноза, особенно когда другие отличительные особенности заболевания не выявлены [10].…”
unclassified
“…Хотя эти нарушения со временем разрешаются, они могут затруднить дифференциальную диагностику [10]. Нейтропения может быть важным ключом к постановке диагноза, особенно когда другие отличительные особенности заболевания не выявлены [10]. Нейтропения служит наиболее частым гематологическим расстройством, встречающимся у 88-100% пациентов [11].…”
unclassified